A COMPARATIVE STUDY OF EFFICACY AND SAFETY AMONG METFORMIN WITH SITAGLIPTIN, METFORMIN WITH VOGLIBOSE, AND METFORMIN WITH GLIMEPIRIDE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - P, Kala; R, Jamuna Rani; Js, Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Type 2 diabetes mellitus (DM) is a most common metabolic disorder. The present study aimed to compare the efficacy and safety among metformin with sitagliptin, metformin with voglibose, and metformin with glimepiride in patients with type 2 DM. Methods: This study was a prospective, randomized clinical trial study, conducted in patients attending the diabetology outpatient department of SRM Medical College Hospital and Research Center, Potheri, Kancheepuram, Tamil Nadu, from January 2013 to January 2014. The patients were randomized into three groups with 40 patients in each group. Fasting plasma glucose (FPG), 2 hrs postprandial plasma glucose (PPG), and hemoglobin A1c (HbA1c) level were assessed in all the patients before starting the treatment. In Group I, patients were prescribed metformin 500 mg with sitagliptin 50 mg, in Group II, patients were given metformin 500 mg with voglibose 0.2 mg, and in Group III, patients were put on metformin 500 mg with glimepiride 1 mg in the fixed combination. The outcome of the therapy was based on the level of improvement in the blood parameters. Results: There was a significant reduction of FPG level seen in all three groups (p value - Group I <0.0001, Group II < 0.005, and Group III <0.0001). Group I and III showed significant reduction of PPG with p value <0.0001. There was a significant reduction of HbA1c seen in all the three groups (p<0.0001). Conclusion: From the results of this study, it could be concluded that all the three groups were comparable in their efficacy.